A revision of the endemic Chinese genus Cornopsylla (Hemiptera: Psyllidae), with potential pests on Zanthoxylum (Rutaceae) - Luo, Xinyu (Zootaxa, 2013)
The endemic Chinese psyllid genus Cornopsylla Li is reviewed with a revised generic diagnosis. Cornopsylla zanthoxylae Li and C. trichotoma Li are redescribed, and Cornopsylla magna sp. nov. and C. rotundiconis sp. nov. are described. Keys to adults and nymphs of this genus are given, and the systematic position of Cornopsylla is reviewed. The potential of Cornopsylla spp. as major pests on cultivated Zanthoxylum is discussed. Psylla sarcospermae (Li) comb. nov. is proposed for this species that does not share the generic characters of Cornopsylla.